Geochemistry and δ^1?O G.ruber records of sediment cores MP50PC, MP39PC and MP37PC - Amalia Filippidi; Gert J de Lange (PANGAEA, 2018)
Eastern Mediterranean thermohaline circulation is directly influenced by mid- and low-latitude climate systems. The dramatic paleoclimate changes during the last African Humid Period (~10-6ka BP) were captured in Mediterranean sediments as the distinctly organic-rich unit sapropel S1. Here, deep-water formation variability during S1 deposition, is reconstructed. We use geochemical records of three cores along a bathymetric transect (775-1359-1908m water depth), at the transition between the Adriatic deep-water formation area and the Eastern Mediterranean. In all three cores, sedimentation rates are distinctly higher during S1, corresponding with enhanced run-off emanating from the Adriatic hinterland. Hence, major run-off did not only come from southern, but also from northern borderlands in this period. During sapropel formation, enhanced levels of primary productivity occurred in the surface waters and oxygen-depleted conditions in the bottom-waters for all sites. Conditions for sediment and bottom-water below ~1.4km water depth were sulphidic throughout S1, but for intermediate depth (775m) were anoxic only during the first part (S1a). Bottom-water oxygenation interrupted S1 formation at water depths down to ~1.4km, during two brief episodes, at 8.2 and 7.4 cal.ka BP. From the 7.4 cal.ka BP ventilation onward, the transition to more oxygenated bottom-water conditions was more progressive for the intermediate water depth site (775m) than for the deeper sites. Conditions remained fully oxic for all water depths following the S1-MarkerBed ventilation event. Possibly the onset of continuously oxic conditions started slightly earlier at intermediate depth (775m; 6.6±0.3 cal.ka BP) than at greater depths (1358m, 1908m; 6.0±0.3 cal.ka BP).
Supplement to: Filippidi, A; de Lange, GJ (2019): Eastern Mediterranean Deep Water Formation During Sapropel S1: A Reconstruction Using Geochemical Records Along a Bathymetric Transect in the Adriatic Outflow Region. Paleoceanography and Paleoclimatology, 34(3), 409-429, https://doi.org/10.1029/2018PA003459